Analysis of Factors Affecting The Index Human Development with Domestic Products Gross Regional as The Intervening Variable (Empirical Study in Regencies and Cities in Central Java 2017-2019) - Ichdiat Wahyu Pratama; Lintang Kurniawati (Prosiding University Research Colloquium, 2022)
This study aims to examine and analyze the effect of Regional Original Income, and General Allocation Funds on the Human Development Index with Gross Regional Domestic Product as an intervening variabel in districts/cities in Central Java in 2017-2019. The approach in this research is to use a descriptive approach. Descriptive method aims to determine the relationship and a deeper nature between variabels. The data analysis method used is the multiple regression method and path analysis is used to test the hypothesis. The results of the study show that the Regional Original Income has no effect on the Human Development Index. The General Allocation Fund has an effect on the Human Development Index. Meanwhile, Regional Original Income has an effect on the Human Development Index through Gross Regional Domestic Product. The General Allocation Fund has no effect on the Human Development Index through Gross Regional Domestic Product.